Prinsip Itikad Baik Terhadap Merek MS Glow - Rachman, Taslim Abd.; Alauddin, Rusdin; Alwan, Sultan (Legal Spirit, 2024)
Legal protection is an important aspect that needs to be considered in the controversy between MS Glow and PS Glow trademarks. PT Kosmetika Global Indonesia, the MS Glow brand holder that has registered its brand with the Director General of Intellectual Property Rights, requires adequate legal protection. The public sees that the products of the MS Glow brand are better known than the products of the PS Glow brand, and there is a view that PS Glow is trying to hijack the popularity of MS Glow. Through normative juridical legal research, it was found that in the context of the principle of good faith, MS Glow is entitled to legal protection as a brand owner. The brand owner has the exclusive right to the use of its brand and the government is responsible for ensuring this protection. The judge's decision in the dispute between the MS Glow and PS Glow trademarks (Decision Number 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga.Sby) has fulfilled the principle of legal certainty. The judge refers to Law Number 20 Year 2016 on Trademark Registration and Geographical Indications as well as the principle of "first to file". However, the decision has not fully reflected justice and expediency. In the context of trademark registration, the "first to file" principle needs to be evaluated by the government to make it fairer. The lengthy trademark registration process must pay close attention to every detail, the Director General of IPR must be more active in socializing Law Number 20 Year 2016, including the principle of "first to file" to the public so that understanding of the trademark and the registration process becomes better.